2023
DOI: 10.1108/ijbm-11-2022-0496
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of the subjective financial well-being during the coronavirus pandemic: a latent transition analysis

Abstract: PurposeThe authors seek (1) to identify the profiles of subjective financial well-being (SFWB) of bank customers before and during the coronavirus disease 2019 (COVID-19) pandemic, (2) to analyze the transition to profiles of lower SFWB during the pandemic and (3) to identify the factors driving such transitions.Design/methodology/approachThe authors surveyed five countries during 2019 and 2020 to measure SFWB. The authors applied latent class analysis (LCA) to identify profiles of bank customers according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Knowing the importance of financial well-being, there are investigations that try to measure it through a questionnaire; in this way, certain measures have been identified in the scientific literature, such as the Perceived Financial Well-being Scale (PFWBS) proposed by Viera et al, (2023) made up of 34 items and 04 dimensions, which are: financial security, financial tranquility, financial freedom and satisfaction with financial management ; from another instance, Nguyen (2021) applied the financial well-being scale made up of 04 items in his study. In addition, (Losada-Otálora et al, 2023)established the SGWB scale that aims to measure financial well-being through 04 dimensions: control over finances, ability to absorb financial shocks, ability to follow financial goals, and freedom financial. Prawitz et al, (2006) reported on the same variable, identifying a construct made up of 08 items called InCharge Finance Distress / Financial Wellbeing (IFDFW).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the importance of financial well-being, there are investigations that try to measure it through a questionnaire; in this way, certain measures have been identified in the scientific literature, such as the Perceived Financial Well-being Scale (PFWBS) proposed by Viera et al, (2023) made up of 34 items and 04 dimensions, which are: financial security, financial tranquility, financial freedom and satisfaction with financial management ; from another instance, Nguyen (2021) applied the financial well-being scale made up of 04 items in his study. In addition, (Losada-Otálora et al, 2023)established the SGWB scale that aims to measure financial well-being through 04 dimensions: control over finances, ability to absorb financial shocks, ability to follow financial goals, and freedom financial. Prawitz et al, (2006) reported on the same variable, identifying a construct made up of 08 items called InCharge Finance Distress / Financial Wellbeing (IFDFW).…”
Section: Introductionmentioning
confidence: 99%